The strengths and weaknesses of bedside electronic systems for recording transfusion-related patient observations - Turner, S; Noel, S; Murphy, M; Watkinson, P (Wiley, 2016)
Blood product administration is associatedwith many risks including acute transfusion reactions. To enable detection of adverse reactions so that necessary treatment can be given, the patient should have their observations (i.e. blood pressure, temperature, pulse and respiratory rate) monitored closely before, during and after the transfusion of blood products. An electronic bedside transfusion process (BloodTrack, Haemonetics) has been used at this institution for over 10 years and enables patient observations to be recorded during the transfusion process. The trusthas developed and installed an electronic bedside observations recording process, System for Electronic Nursing Documentation (SEND), with integrated track and trigger calculation and alerts. SEND has been shown to make recording observations more efficient and has demonstrated successful user uptake